Stroke in neurological services in Italy - Fabrizio Antonio De Falco; Maurizio A. Leone; Ettore Beghi (MDPI AG, 2009)
o assess the stroke workload of Italian neurological services and to correlate it with indicators of each hospital's emergency setting. A semi-structured questionnaire was sent to the 220 neurology units (NU) located in hospitals with an emergency room (ER) (155 responders, 71%). Stroke was the most common discharge diagnosis (29%) (273 patients/year/NU on average) and condition requiring consultation in ER (28%). A stroke unit was available in 28% of NU, bedside monitors in 45%, a 24 hour/day and 7 day/week (24/7) CT scan in 90%, a 24/7-MRI in 32%, a 24/7 on-duty neurologist in 36%. The stroke workload was correlated only with the number of ER consultations per year, and marginally to the presence of stroke units and the number of monitored beds in the univariate, but not in the multivariate analysis. The stroke workload in Italian NU is very high, but is largely unrelated to their structural and functional characteristics, in contrast with the international indications requiring several essential criteria for the best hospital management of all stroke patients.